Master narratives and narratives as told by people with mental health and drug problems (Journal of Comparative Social Work, 2010)
This article examines the role of master narratives in self-narratives told by people with both mental health and drug problems. It is based on stories told by people who have both mental health and drug problems. However, their substance abuse has become their most dominant characteristic in their lives. The storytellers or the interviewees attempt to describe their background, their experience and what they call churning thoughts, while their stories are also infiltrated and dominated by master narratives about the drug abuser.